Dance in the Educational Context - Gregorio Vicente Nicolás; Nuria Ureña Ortín; Jesús Carrillo Vigueras (FEADEF, 2010)
This paper provides an overview of the phenomenon of dance in the field of education. At first, it is made a presentation of the different components or aspects of human beings on that dance impacts in a more obvious way. Subsequently, we present a review of the definitions proposed by different authors that we consider most relevant and it is included a personal definition of the concept. It also highlights the contributions of dance to education in terms of social, physical, intellectual and emotional development and identifies the major problems that this discipline has had to be included as a subject: lack of teacher training, lack of adequate space and resources and gender discrimination. Finally, it concludes with a reflection on the most appropriate forms of dance in the educational context.